OPTIMALISASI PENULISAN ILMIAH MELALUI PEMBELAJARAN BAHASA INDONESIA BERBASIS PROYEK - Hudaa, Syihaabul; Mahsusi, Mahsusi; Nuryani, Nuryani (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
The progress of education is characterized by a breakthrough in the application of knowledge. However, until now, linguistic competence in Indonesian classes has not had effective standardization, so writing articles in journals is still considered difficult. The purpose of this article is to discuss the improvement of scientific writing skills for journal articles through an output-based learning model. The source of data in this study is Accounting students in the 6th semester at UIN Jakarta. The data in this study are in the form of student outcomes produced, namely articles in national journals. Standardization of learning success assessment is based on three indicators, namely: published articles, LoA, and in process. Based on the research conducted by the researcher, it was concluded that out of 57 Accounting students, there were two students who were considered not graduating. One student did not pass because he did not do the output of the Indonesian language course, the other one withdrew from the Indonesian language class. Overall, there were 13 articles produced in groups by 6th semester students. Twelve articles have been published, and one article has just received LoA.